Improving elementary childcare system in women's growing economic participation - Sungmin Han (Korea Development Institute (KDI), 2021)
Despite women's growing economic participation, female employment rates vary considerably across age groups. Women in their 30~40s exhibit the lowest rates, mainly due to the lack of policy support targeting women with dependent children in elementary school. The Korean government has sought to address this by expanding public childcare, but problems like childcare void and high dependence on private education persist. Amid rising social demands for childcare services, taking policy actions to enhance the quality and quantity of public childcare and overhaul its legal framework is of vital importance and requires immediate attention.
Keywords: 330